CALCULATION OF OPTIMAL TEMPERATURE OF AIR HEATING IN RECUPERATOR AT THE EXAMPLE OF OPERATING THERMAL FURNACE OF THE MODERN MACHINE-BUILDING PLANT FROM TECHNICAL-ECONOMICAL POINT OF VIEW - V. I. Timoshpolskij; D. V. Mendeleev; M. L. German; I. A. Trusova; S. V. Korneev (Литьë и металлургия, 2008)
The methods of determination of optimal temperature of air heating in regulating device of heating and thermal furnaces, functioning in machine-building and metallurgy are given.